Success strategy of female ulama leadership to advance Salafiyah Islamic Boarding School amid patriarchal resistance - Fauzan, Ahmad; Rahayu, Lina Meilinawati; Muhtadin, Teddi; Hazbini, Hazbini (Indonesian Journal of Islam and Muslim Societies, 2025)
This article describes the success strategy of a female ulama leader (Nyai) in leading and advancing Salafiyah Islamic boarding schools (Salafiyah Pesantren) amid patriarchal resistance. The female ulama is Nyai Masriyah Amva, the head of pesantren Kebon Jambu Cirebon. The primary objective of this research is to investigate the success strategies employed by women’s leadership in Salafiyah Pesantren, and to provide a strategic vision for women living in a patriarchal environment to become more confident in taking action. Furthermore, this article is at least part of an effort to challenge the perception of pesantren salafiyah as patriarchal. The use of qualitative methods, particularly in ethnographic studies, serves to understand the meaning of individuals or groups of people who are considered to be affected by social problems in humanity through observation, interviews, and documentation. The result is that everything considered cultural or taboo is not necessarily part of the actual teachings of “Islamic teachings”. Thus, being a leader in a minority setting, she actually has more opportunities to work. All her strategies represent the resistance to patriarchal culture, though they require careful planning. In short, she rejects the patriarchal culture, but can still be accepted around her, even in the way that Nyai Masriyah Amva can advance herself and her pesantren. Artikel ini memaparkan strategi kesuksesan pemimpinan ulama perempuan (Nyai) dalam memajukan pesantren salafiyah di tengah perlawanan patriarki. Beliau adalah Nyai Masriyah Amva sebagai pimpinan Pesantren Kebon Jambu, Cirebon, Indonesia. Tujuan dari penelitian ini adalah untuk mempelajari strategi kesuksesan kepemimpinan perempuan di pesantren salafiyah, serta memberikan wawasan strategis bagi perempuan yang hidup di lingkungan patriarki untuk menjadi lebih percaya diri dalam melakukan sesuatu. Selain itu, dengan adanya artikel ini setidaknya bagian dari usaha untuk mengikis pemahaman tentang pesantren salafiyah yang patriarki. Metode kualitatif dengan studi etnografi digunakan untuk mengetahui makna individu atau kelompok orang yang dianggap berasal dari masalah sosial kemanusiaan melalui observasi, wawancara, dan dokumentasi. Adapun hasil penelitian ini adalah bahwa segala sesuatu yang dianggap budaya atau tabu belum tentu menjadi bagian dari ajaran “ajaran Islam”. Menjadi pemimpin di lingkungan minoritas, sebenarnya seseorang memiliki lebih banyak kesempatan untuk berkarya. Semua strategi yang dilakukannya merupakan bagian dari perlawanan terhadap budaya patriarki. Singkatnya, seorang nyai dapat menolak budaya patriarki, namun tetap bisa diterima di lingkungan sekitarnya, bahkan bisa memajukan dirinya dan pesantrennya.